POLITIK LUAR NEGERI CHINA â€œNEW SECURITY CONCEPTâ€ PADA HUBUNGAN CHINA-RUSIA DI MASA PRESIDEN HU JINTAO - Herning Suryo, Septian Eko Cahyono, Christy Damayanti & (Transformasi, 2015)
This research entitled "China's Foreign Policy" New Security Concept "In the China-Russia Relations In The President Hu Jintao". New Security Concept arise when the collapse of the Soviet Union that led to changes in the international political situation of bipolar becoming multipolar. China with New Security Concept trying to create security conditions in the region and make Russia a strategic partnership to meet its domestic needs, both in energy and military as well as counterbalance US hegemony in Central Asia and East Asia. This study aims to explain how the foreign policy of New Security Concept of China to the Chinese-Russian relations during President Hu Jintao. This research uses descriptive qualitative research method in which the author describes and outlines the relevant data for the study and then the data is reduced further presented and verified in order to obtain valid results related research. From these research it can be concluded that China continues to meet its national interests always forward peacefully and maintain security and stability in the region. China is also cooperating with Russia as one of the influential countries in the region to offset the hegemony of the United States so that China can stay focused on economic development in the country.Keywords: New Security Concept, Security, China-Russia relations, the US hegemony.